STRATEGI KOMUNIKASI DUTA GENRE KABUPATEN TANAH DATAR DALAM UPAYA PENDEWASAAN USIA PERKAWINAN DI KECAMATAN LIMA KAUM - Ryan Hajusa Karilda; Syafriwaldi Syafriwaldi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem of this research is how communication strategy of the Tanah Datar Genre Ambassador on maturing the age of marriage in the Lima Kaum District. This research aims to find out and explain what are the efforts to mature marriage in Lima Kaum District, the media used and what are the supporting and inhibiting factors of it. This research uses the descriptive qualitative method. The data was collected with observation, documentation and interviews. From this research, it can be concluded that, Firstly, the communication strategy of the Tanah Datar Genre Ambassador in disseminating work programs about efforts to mature the marriage age in Lima Kaum District is to carry out the Tanah Datar Genre Ambassador flagship program in the form of socialization to schools, information centers for adolescent and society counseling in the family planning village in Lima Kaum Disct so that the desired goals are achieved. Secondly, because of the Covid19 pandemic state, the media used such as Instagram in informing related lessons, need to be upgraded. Thirdly, the inhibiting factor is the socialization is still not optimal on the marriage age maturation program, the covid19 pandemic becomes an obstacle too. Meanwhile, the supporting factors include support from the government such as the village community empowerment service, population control and family planning, as well as support from various figures and parties